2022
DOI: 10.3390/ijfs10040093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bank Efficiency on the Profitability of the Banks in India: An Empirical Analysis Using Panel Data Approach

Abstract: This study aims to determine the impact of banking efficiency on the profitability of the Indian banking division. The ratios (key variables) used in the study are mentioned by the Reserve Bank of India—RBI (Central bank of India). Through a quantitative approach, pooled panel regression, univariate analysis, correlation, and descriptive statistics models are used by taking annual data of the Indian banking division from 2001 to 2020 available on the Thomson Reuters (Refinitiv) Database. Unbalanced cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
5
0
9
Order By: Relevance
“…Our findings are in line with Bawa et al (2019). Similarly, Dsouza et al (2022) found that CI has a negative effect on the ROE of banks in India. However, the findings of this study regarding the insignificance of CAR in affecting ROA and ROE are somewhat different from previous studies, which have found that CAR is a significant indicator of credit risk that affects the financial performance of banks.…”
Section: Conclusion Limitations and Future Scopesupporting
confidence: 90%
“…Our findings are in line with Bawa et al (2019). Similarly, Dsouza et al (2022) found that CI has a negative effect on the ROE of banks in India. However, the findings of this study regarding the insignificance of CAR in affecting ROA and ROE are somewhat different from previous studies, which have found that CAR is a significant indicator of credit risk that affects the financial performance of banks.…”
Section: Conclusion Limitations and Future Scopesupporting
confidence: 90%
“…European banks were discussed by Kozak and Wierzbowska (2022). Asian banks were analyzed by Nguyen and Le (2022) and Dsouza et al (2022). Vietnamese banks were evaluated by Pham et al (2022), and sub-Saharan African banks were assessed by Taylor et al (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous mathematical and statistical techniques were used to draw this conclusion. Not only the aforementioned authors performed profitability indicator analyses, but in their analysis of Indian banks, Dsouza et al (2022) employed additional methods, including panel regression, one-dimensional analysis, and descriptive statistics. In the US, however, Chue and Xu (2022) used the model of Hou, Xue, and Zhang, which solved aggregate profitability and investment in assets and showed high predictive power.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But, credit risk, cost of fund, nonperforming assets and consumer price index have significantly negative influence to the profitability while bank size and ratio of priority loan to total loans do not have any impact towards profitability. Dsouza et al (2022) found that cost to income ratio has a significant negative impact to the return on assets and net interest margin in Indian banks from the analysis of data 2001 to 2020. The staff expenses to total expenses ratio has a significant positive impact on return on assets but it has positive insignificant impact to the net interest margin.…”
Section: Review Of Literaturementioning
confidence: 99%